2018
DOI: 10.1177/0271121418777290
|View full text |Cite
|
Sign up to set email alerts
|

Update on the EMI for Infants and Toddlers

Abstract: Movement is a critical factor in brain development and codevelops with cognition and language (Iverson, 2010; Leonard & Hill, 2014). Reports indicate that movement mediates exploration of the environment which, in turn, is related to more enhanced and differentiated early cognitive development (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…The finding provided support to ESIs claim of construct validity because lower ESI performance was consistent with expectation of children with a documented disability. Lower performance by infants and toddlers with IFSPs have been reported for the other IGDI measures (Early Communication Indicator [ECI]—Greenwood et al, 2010; Early Movement Indicator [EMI]—Greenwood et al, 2018; Early Problem-Solving Indicator [EPSI]—Greenwood et al, 2006). Collectively, these findings represent a further understanding of how social behaviors emerge in the first years as well as how the ESI performs with differences in child respondents and conditions of administration (Carta et al, 2004; Halle & Darling-Churchill, 2016).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The finding provided support to ESIs claim of construct validity because lower ESI performance was consistent with expectation of children with a documented disability. Lower performance by infants and toddlers with IFSPs have been reported for the other IGDI measures (Early Communication Indicator [ECI]—Greenwood et al, 2010; Early Movement Indicator [EMI]—Greenwood et al, 2018; Early Problem-Solving Indicator [EPSI]—Greenwood et al, 2006). Collectively, these findings represent a further understanding of how social behaviors emerge in the first years as well as how the ESI performs with differences in child respondents and conditions of administration (Carta et al, 2004; Halle & Darling-Churchill, 2016).…”
Section: Discussionmentioning
confidence: 92%
“…The Early Social Indicator (ESI ) is one of four Individual Growth and Development Indicators (IGDIs) for infants and toddlers designed for use in MTSS (Carta et al, 2004, 2010). In addition to the ESI, the suite of IGDIs assesses progress in Early Communication (Greenwood et al, 2010), Early Movement (Greenwood et al, 2018), and Early Cognitive Problem-Solving (Carta et al, 2004). The ESI is an observation of a child’ social engagement with a familiar adult and peer during a 6-min play session with an authentic toy set.…”
Section: The Early Social Indicatormentioning
confidence: 99%
“…Prior studies have found that the observed dynamic relationship between these key skills is consistent with language development theory (Greenwood et al, 2013). For example, analyses of key skill growth trajectories consistently show accelerated rates of vocalizations until about 14 to 20 months of age, followed by a rapid decrease as single words develop; a similar rise and fall is observed for single words at about 30 to 36 months of age as children begin to use more multiple words (Greenwood et al, 2010, 2018).…”
Section: The Early Communication Indicator For Infants and Toddlersmentioning
confidence: 97%
“…Example applications of the ALD can be found in Greenwood, Carta, Walker, Hughes, and Weathers (2006, 2018, 2020), which studied the development of children's communication, movement, and social skills (e.g., Individual Growth and Development Indicators; Carta et al., 2010). In the studies, they used ALD to collect data across a wide age range (e.g., 6–36 months of age) by only measuring the participants for a few occasions (e.g., 3–5), allowing examining the change trajectories of these skills over the whole age span (Greenwood et al., 2006, 2018, 2020).…”
Section: Wave Level Planned Missingness Designsmentioning
confidence: 99%